KOMUNIKASI BUDAYA DALAM MENINGKATKAN PARTISIPASI PEMILIH DI KOTA PARIAMAN - Widya Hasan; Asmawi Asmawi; Najmuddin Rasul (Universitas Andalas, 2018)
Downward trend voter participation in the election of the Governor and Deputy Governor of West Sumatra Province in Kota Pariaman needs special attention, because percentage of voters who use votes at polling stations is still a benchmark for the amount of public trust in the elected regional heads through the election mechanism. Therefore is needed communication pattern that can provide understanding and educating the public about the importance of exercising voting rights during elections. Like a pattern of socialization that puts forward a cultural approach (Local Wisdom) that can inspire people to use their voting rights at TPS. This research method is descriptive qualitative that aims to understand and interpretation the meaning of events, interactions and human behavior through communication with cultural approaches. That form of 'Ciloteh Lapau' which is one of the media for election socialization and education to increase voter participation in Kota Pariaman.